Changes in the selection criteria of a management consultant in north-eastern hungary 2001-2016 - Ágnes Tokár-Szadai (Journal of Contemporary Economic and Business Issues, 2018)
The Institute of Business Sciences of the University of Miskolc conducted a survey in 2001, 2005-06, 2011-12 and 2015-16 among consultants and their clients. In this study, the author presents on the basis of which aspects the clients choose a consultant, what the difference is between the opinion of the consultants and their clients, how these aspects changed in the examined period, and how the consultants would be able to meet their clients' requirements. According to the surveys, consultants - in the case of most selection criteria - see the importance of the single criteria similarly to their clients and perceive its change similarly. More flexible, more complex, and more solution orientated proposals would make the consultants more convenient to their clients.
Keywords: L84; M53; O15; 330; management consultant; selection criteria; clients' requirements; change 2001-2016; Client; North-Eastern Hungary